Formalisation of informal collectors under a dual-recycling channel: A game theoretic approach. Issue 5 (May 2020) - Wang, Juntao; Li, Wenhua; Mishima, Nozomu; Adachi, Tsuyoshi
Formalisation of informal collectors is beneficial for economical, environmental and social sustainability. Through dividing collectors and recyclers, a benchmark model consists of competitive dual formal and informal channels is established to quantitatively analyse the possibility of formalising informal collectors and study the formalisation extent. This study comprehensively compares the effects of respective subsidy or punishment targeting at collectors or recyclers in the extended policy model. The subsidy delay used to represent the response speed of the subsidy system is first included. This study indicates the influences of different factors on formalisation activity, including bargaining power, reluctance of informal collectors and recycling cost of formal channels. The policy model concluded that the subsidy on informal collectors or formal recyclers (punishment on informal collectors or informal recyclers) presents no difference regarding the formalisation extent. Based on numerical data, we studied the formalisation extent for the context of China and visualised the effects of different policies. The decremental effect of subsidy and the incremental effect of punishment are concluded in a formalisation activity. This study fills the gap of a quantitative study on formalisation activity and the results will comprehend the promotion of the formalisation of informal collectors.